2005
DOI: 10.1128/jvi.79.23.14708-14718.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Neuronal Host Cell Factor-Binding Protein Zhangfei Inhibits Herpes Simplex Virus Replication

Abstract: During lytic infection in epithelial cells the expression of herpes simplex virus type 1 (HSV-1) immediateearly (IE) genes is initiated by a multiprotein complex comprising the virion-associated protein VP16 and two cellular proteins, host cellular factor (HCF) and Oct-1. Oct-1 directly recognizes TAATGARAT elements in promoters of IE genes. The role of HCF is not clear. HSV-1 also infects sensory neurons innervating the site of productive infection and establishes a latent infection in these cells. It is like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 45 publications
2
41
0
Order By: Relevance
“…The bZIP protein SMILE has been reported to regulate the transactivation of several transcription factors, including ERs, host-cell factor, CREB3, and ATF4 (6,(17)(18)(19). Recently, we have reported that SMILE acts as a novel corepressor of nuclear receptors GR, CAR, and HNF4␣ (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bZIP protein SMILE has been reported to regulate the transactivation of several transcription factors, including ERs, host-cell factor, CREB3, and ATF4 (6,(17)(18)(19). Recently, we have reported that SMILE acts as a novel corepressor of nuclear receptors GR, CAR, and HNF4␣ (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, SMILE cannot bind to DNA as homodimers, although it can homodimerize like other bZIP proteins (15,17). SMILE has been implicated in herpes simplex virus infection cycle and related cellular processes through its association with herpes simplex virus-related host-cell factor and CREB3 (17,18).…”
mentioning
confidence: 99%
“…While Zhangfei can activate gene expression through factors such as p53 2 and ATF4, 3 it suppresses the activity of a number of transcription factors, which includes nuclear receptors, [4][5][6] bLZip containing proteins such as CREBH, 7 Luman/CREB3, 8 Xbp1, and SMAD 1,5,8, 9 and the HCFbinding VP16. 10 Zhangfei also has a profoundly suppressive effect on the unfolded protein response (UPR), at least partly because it targets Xbp1s, an important UPR mediator, for proteasomal degradation. 11 We have detected Zhangfei protein in differentiated neurons, but not in developing neurons or cells of neuronal tumors, 10 nor in osteosarcoma cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…10 Zhangfei also has a profoundly suppressive effect on the unfolded protein response (UPR), at least partly because it targets Xbp1s, an important UPR mediator, for proteasomal degradation. 11 We have detected Zhangfei protein in differentiated neurons, but not in developing neurons or cells of neuronal tumors, 10 nor in osteosarcoma cell lines. The ectopic expression of Zhangfei in several tumor cells lines derived from medulloblastomas (ONS-76, UW228 12 ) and osteosarcomas (D-17 13 ) causes the cells to stop growing and display markers of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Small heterodimer partner-interacting leucine zipper protein (SMILE), including two alternative translation-derived isoforms, SMILE-L (CREBZF: long form of SMILE) and SMILE-S (Zhangfei: short form of SMILE), has been classified as a member of the CREB/ATF family of basic regionleucine zipper transcription factors. However, SMILE cannot bind to DNA as a homodimer (10)(11)(12). SMILE has also been reported to function as a coactivator of activating transcription factor 4 or as a corepressor of host cell factor-binding transcription factor (13,14).…”
mentioning
confidence: 99%